Anatomical variant of the femoral-cutaneous nerve as a cause of meralgia paresthetica - Martínez, Fernando (Revista Argentina de Neurocirugía, 2024)
Background: paresthetic meralgia (PM) is a neuropathy caused by entrapment of the femoral cutaneous nerve in its passage from the pelvis to the inguinal-femoral region. Although this condition is not very common, it is recognized by its clinical presentation characterized by pain or paresthesia in the anterolateral aspect of the thigh. Objectives: to describe a case of MP caused by an anomalous course of the femoral cutaneous nerve. Case description: a 23-year-old woman, with pain and paresthesia in the lateral aspect of the right thigh for 8 months. An anesthetic block was performed below and within the anterior superior iliac spine (ASIS), with improvement of the symptoms. The symptoms were then reinstalled, so decompression of the femoral cutaneous nerve was considered. Surgery: the nerve was identified reaching the pelvis outside the ASIS. It was dissected and external neurolysis and transposition of the nerve was performed, achieving complete improvement of the symptoms in the third week. Conclusion: PM is a rare entrapment neuropathy that responds to medical treatment in most cases. Some of its most common causes are anatomical variants of the nerve, which should be known by the peripheral nerve surgeon.